2006
DOI: 10.1177/019027250606900404
|View full text |Cite
|
Sign up to set email alerts
|

Traditional and Health-Related Philanthropy: The Role of Resources and Personality

Abstract: I study the relationships of resources and personality characteristics to charitable giving, postmortem organ donation, and blood donation in a nationwide sample of persons in households in the Netherlands. I find that specific personality characteristics are related to specific types of giving: agreeableness to blood donation, empathic concern to charitable giving, and prosocial value orientation to postmortem organ donation. I find that giving has a consistently stronger relation to human and social capital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
237
4
18

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(277 citation statements)
references
References 54 publications
18
237
4
18
Order By: Relevance
“…Using a two stage least squares regression model, two studies still find a positive association between church attendance and giving (Lunn et al 2001;Sullivan 1985). Bekkers (2006b) found that empathy and verbal proficiency affects giving partly through church attendance.…”
Section: Religionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a two stage least squares regression model, two studies still find a positive association between church attendance and giving (Lunn et al 2001;Sullivan 1985). Bekkers (2006b) found that empathy and verbal proficiency affects giving partly through church attendance.…”
Section: Religionmentioning
confidence: 99%
“…Positive relations between philanthropy and level of education are found in most empirical studies that include education (Apinunmahakul & Devlin 2004;Banks & Tanner 1999;Bekkers 2003;2006b;Bekkers & De Graaf 2006;Bielefeld et al 2005;Brooks 2004;Brown 2005;Brown & Ferris 2007;Brown & Lankford 1992;Carroll et al 2006;Chang 2005a;Chua & Wong 1999;Duncan 1999;Eschholz & Van Slyke 2002;Feldman 2007;Gruber 2004;Houston 2006;Jones & Posnett 1991a;Kingma 1989;Lyons & Nivison-Smith 2006;Lyons & Passey 2005;Matsunaga 2006;McClelland & Kokoski 1994;Mesch et al 2006;Olson & Caddell 1994;Pharoah & Tanner 1997;Reece & Zieschang 1985;Reed & Selbee 2002;Rooney et al 2001;Schiff 1990;Schlegelmilch et al 1997a;Sokolowski 1996;Tiehen 2001;Todd & Lawson 1999;Van Slyke & Brooks 2005;Wiepking & Maas 2006;Wilhelm et al 2006;Yamauchi & Yokoyama 2005;Yavas et al 1981). Higher levels of education are also associated with giving a higher proportion of income …”
Section: Educationmentioning
confidence: 99%
“…Empathic concern, or ''the tendency to experience feelings of sympathy and compassion for those in need'' (Davis 1994:57), has been the subject of extensive study over the last 20 years, and numerous studies have found a connection between empathic concern and prosocial behaviors (Bekkers 2005(Bekkers , 2006Davis 1994;Davis et al 1999Davis et al , 2003Einolf 2010;Penner et al 1995;Penner and Finkelstein 1998;Penner 2002). One reason that daily spiritual experiences may cause individuals to help others is that they may encourage the development of empathy.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an increasingly important and largely underdeveloped financial stream for public higher education institutions is philanthropy [6][7][8], that is donations from the general public to the universities for either specific or non-tagged purposes. Philanthropy is associated with the action of "expressing love to mankind" [9] and is often focused towards improving humanity rather than solely serving the needs of the poor. In the context of defining the action of giving to higher education, Cascione [10] stated:…”
Section: Introductionmentioning
confidence: 99%